Erratum to "An in silico strategy to explore neuroprotection by quercetin in cerebral ischemia: A novel hypothesis based on inhibition of matrix metalloproteinase (MMPs) and acid sensing ion channel 1a (ASIC1a)" [Med. Hypotheses 79 (1) (2012) 76-81] - Pandey A.K.; Verma S.; Bhattacharya P.; Paul S.; Mishra A.; Patnaik R. (My University, 2025)
[No abstract available]